Motivasi, Lingkungan, dan Disiplin Kerja terhadap Kinerja Karyawan PT Dolphin Putera Sejati Sukoharjo - Wahyu Indriyani; Istiatin Istiatin; Sarsono Sarsono (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
ThePpurpose of this research is to determine the relationship of the influence of motivation, environment, and work discipline on the performance of PT Dolphin Putera Sejati Sukoharjo employees. The method used on this research is descriptive quantitative with SPSS 25 tested on 115 respondents from the results using incidental sampling sampling technique. This study uses multiple linear regressionOanalysis techniques regression test, F test, T test, and also the coefficient of determination. The results of this research showothat simultaneously motivation, environment, and work discipline have a major impact onOemployee performance, which is 67,7% and the remaining 32,3% is influenced by other factors such as leadership, work commitment, job satisfaction, and so on. Keywords : Motivation, Environment, Discipline